Islamic attributes of destination: Construct development and measurement validation, and their impact on tourist satisfaction - Battour, Mohamed; Battor, Moustafa; Bhatti, Muhammad Awais (John Wiley & Sons, 2013)
The objectives of the paper are to first develop a measurement scale for Islamic attributes of destination and then to investigate the influence of Islamic attributes on overall tourist satisfaction.This study followed the sequence of steps that should be performed in developing measures of constructs. The measurement was tested and found to be both reliable and valid.The study found positive relationship between Islamic attributes of destination and overall tourist satisfaction. Important marketing implications are also presented. Copyright © 2013 John Wiley & Sons, Ltd.